Thoracic endovascular aortic repair for avulsion of aortic branches in a trauma patient requiring resuscitative thoracotomy: a case report - Atsushi Tanikawa; Takeaki Sato; Motoo Fujita; Chieri Tsuchiya; Ken Katsuta; Yusuke Suzuki; Kiichiro Kumagai; Yoshikatsu Saiki; Shigeki Kushimoto (Surgical Case Reports, 2022)
Abstract Background Resuscitative thoracotomy is a lifesaving procedure for trauma patients that are hemodynamically unstable. Cross-clamping of the descending thoracic aorta is an essential procedure performed during resuscitative thoracotomy in patients with impending cardiac arrest. Although complications related to resuscitative thoracotomy have been reported, there is no report on avulsion of aortic branches related to cross-clamping of the descending aorta and its appropriate management. Case presentation We present the case of a 42-year-old woman who sustained blunt trauma due to an accidental fall. The patient was hemodynamically unstable and required resuscitative thoracotomy with cross-clamping of the thoracic aorta. However, hemorrhage from avulsion of aortic branches related to aortic cross-clamping was identified. Initially, transcatheter arterial embolization was attempted to achieve hemostasis; however, when that proved ineffective, thoracic endovascular aortic repair was performed, which resulted in successful hemorrhage control without any sequelae. Conclusions Thoracic endovascular aortic repair may be a management option for aortic branch avulsion due to cross-clamping of the descending aorta during resuscitative thoracotomy.